Straightforward synthesis of injectable calcium phosphate cement through novel hydrthermal technique for bone filling materials - Sopyan, Iis; Hablee, Sufiamie; Razali, Nurul Nabilah (2019)
This current research developed calcium phosphate/poly(ethylene glycol) (CPC/PEG) and calcium phosphate/poly(vinyl alcohol) (CPC/PVA) composite bone cements and investigated the physical, mechanical and biological properties of the cement. First part is the synthesis of calcium phosphate cement (CPC) via wet chemical precipitation method by using calcium hydroxide, Ca(OH)2, and diammonium hydrogen phosphate, (NH4)2HPO4. The mixture of calcium and phosphorus solution refluxed at 90°C. The production of CPC has been done by mixing the wet chemical precipitation derived hydroxyapatite (HA) powder with distilled water at certain powder-to-liquid (P/L) ratio, varied at 1.0, 1.3, 1.5 and 1.7. CPC/PEG composite was produced by mixing the synthesized powder with liquid phase containing PEG at different PEG amounts, varied at 1, 2, 3, 4 and 5 wt%. XRD and FTIR confirmed the formation of pure HA. Morphology analyses of FESEM and TEM illustrated the formation of agglomerated nanorod shape HA particles with size of 150-300 nm length and 10-30 nm width. Afterwards, the produced CPC was investigated for injectability, setting time, compression strength, porosity, anti-washout and cell proliferation capacity. The results of this study revealed that higher P/L ratio contributed to better setting time and compressive strength of CPC but worsen its injectability. The best properties achieved by CPC with the P/L ratio of 1.3, which shows 82.5% paste injectability, 88 min initial setting time, 228 min final setting time and 1.344 MPa compressive strength. The study on the effect of PEG on CPC properties has shown significant improvement in setting time, injectability and mechanical strength. The incorporation of 2% PEG into CPC with the P/L ratio 1.3 shows properties improvement with 85.9% paste injectability, 60 min initial setting time, 209 min final setting time and 1.781 MPa compressive strength. All CPC compositions demonstrated an excellent performance since no cement dissolution or broken throughout 28 days soaking in Ringer’s solution, except for the CPC/PEG with the P/L ratio of 1.0 with 3, 4, and 5 wt% PEG additions. The cell culture on both CPC and CPC/PEG have proven that the fabricated bone cements show no toxic reaction and cells grow well. The second part is the synthesis of CPC via a straightforward hydrothermal route. Calcium oxide and ammonium dihydrogen phosphate were used as calcium and phosphate precursors. The precursors were refluxed in distilled water at 90-100˚C and dried overnight until the calcium phosphate powder was formed. CPC was then produced by mixing the powder and distilled water at the powder-to-liquid (P/L) ratio of 1.5. The PVA addition to CPC was varied from 1 to 7% (w/w) and its effect was systematically investigated. It was proved that PVA addition up to 7% (w/w) has shortened the setting time but decreased the injectability. The PVA free CPC has the initial and final setting times of 71 and 187 min, respectively and the injectability of 99.92%. The compressive strength also increased with the increasing amount of PVA added in CPC. In addition, soaking CPC in Ringer's solution for 7,14 and 21 days also gave remarkable effects to cohesion, microstructure and mechanical properties of the cements. This present study shows that the fabricated bioactive ceramic matrix composite is suitable for injectable bone cement applications.